Determinants of customer acceptance of e-banking in Iraq using technology acceptance model - Ayad Hameed Mousa; Sundus Hameed Mousa; Mustafa Aljshamee; Intedhar Shakir Nasir (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
Electronic banking (e-banking) is a form of banking in which funds are transferred through an exchange of electronic signals along to the traditional banking process as the exchange of cash, checks, or other types of paper documents. Moreover, the general tendencies of the Iraqi government in line with other countries to adopt e-banking and provide e-services to customers. However, the determinants of e-banking services need to investigate to determine the variables affecting the rate of such adoption. Thus, the main aim of this study is to identify the determinants of e-banking services in Iraq. Hence, this study gives an investigation using the technology acceptance model (TAM) by selecting a sample for many Iraqi banks' customers and staff to determine the determinants of user acceptance of e-banking. A preliminary study was conducted to empirically determine the user acceptance determinants of e-banking. For data collection, a quantitative method was used represented by the questionnaire. The selected sample for the investigation is 200 (customers and staff). Several methods have used for data analysis such as hierarchical regression, one-way ANOVA, descriptive statistics, t-test as well as structural equation modeling (SEM). The obtained outcomes show there are several determinants of e-banking services in Iraq that have determined in this study. Moreover, this study confirms the overcoming of those determinants will give a highly positive impact on e-banking services.